Options and strategies for the conservation of farm animal genetic resources. Report of an international workshop - Gibson, John P.; Gamage, S.; Hanotte, Olivier H.; Iniguez, L.; Maillard, J.C.; Rischkowsky, Barbara A.; Semambo, D.K.; Toll, Jane (SGRP, 2006)
This workshop reviews the options and strategies for the conservation of farm animal genetic resources (FAnGR) and to identify priorities for action. It focusses primarily on the technical needs and opportunities and placed less emphasis on policy and institutional issues. The workshop resulted in eleven major findings and 13 priorities for action. It also identified four broad areas where information and knowledge were lacking. The findings and priorities for action are listed and explained.in this Report.